(untitled) (International Journal of Engineering and Computer Science, 2015)
The green computing is environmentally responsible for all computers and any other technology related resources .Green computing by implementation, includes energy efficiency central processing units (CPUs) ,peripherals and servers. In addition green computing is also used to control energy consumption and improve the disposal of electronic waste (e-waste) .disk drives increases more power , one of the most critical issues of designing modern disk systems is data reliability. The factors that affect the reliability of disk systems is the disk utilization and ages. In the existing work a novel approach called safe utilization zone is introduced to obtain reliability. The energy consumption is obtained by integrating the existing energy consumption algorithm with the novel algorithm. In the proposed work, a novel approach to mixed read/write workloads is introduced. This approach is used to achieve the trade-off between reliability and energy-efficiency and to balance the energy and reliability